La causa morisca en Guerras civiles de Granada: un estudio comparativo entre la primera y segunda parte. The morisco’s cause in Guerras civiles de Granada: a comparative study between the first and second part - Mimura, Tomoko (Anales del Seminario de Historia de la Filosofía, 2006)
The time when Guerras civiles de Granada was written produced a long process of assimilation and acculturation for the moriscos. The occurrences in this process mark the narrative tone of each part of the work, which is, more than a mere reflection of the epoch, an appeal to the contemporaries for consideration of the moriscos’ cause. The first part hints at the same direction as El Abencerraje and the second, Libros plúmbeos.